2013
DOI: 10.18172/cig.2002
|View full text |Cite
|
Sign up to set email alerts
|

Magnetismo y cambios ambientales en registros terrestres: El lago de Marboré, Parque Nacional de Ordesa y Monte Perdido (Huesca)

Abstract: RESUMEN. El estudio de las propiedades magnéticas y sus variaciones en el tiempo en sondeos lacustres permiten deducir cambios paleoambientales

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
(35 reference statements)
0
10
0
2
Order By: Relevance
“…Scientists have studied glaciers in the Marboré Cirque since the mid-19th century (Schrader, 1874), and many subsequent studies examined the status and extent of the ice masses and moraine features deposited during the LIA (Gómez de Llarena, 1936;Hernández-Pacheco and Vidal Box, 1946;Boyé, 1952). More recent studies have established the locations of moraines to deduce the dynamics and extent of LIA glaciers (Nicolás, 1981 and1986;Martínez de Pisón and Arenillas, 1988;García Ruiz and Martí Bono, 2002;Martín Moreno, 2004) and have analyzed environmental changes during the Holocene through the study of sediments in Marboré Lake (Oliva-Urcía et al, 2013) and by dating of Holocene morainic deposits (García-Ruiz et al, 2014).…”
Section: Study Area and Review Of Previous Research On The Monte Perdmentioning
confidence: 99%
“…Scientists have studied glaciers in the Marboré Cirque since the mid-19th century (Schrader, 1874), and many subsequent studies examined the status and extent of the ice masses and moraine features deposited during the LIA (Gómez de Llarena, 1936;Hernández-Pacheco and Vidal Box, 1946;Boyé, 1952). More recent studies have established the locations of moraines to deduce the dynamics and extent of LIA glaciers (Nicolás, 1981 and1986;Martínez de Pisón and Arenillas, 1988;García Ruiz and Martí Bono, 2002;Martín Moreno, 2004) and have analyzed environmental changes during the Holocene through the study of sediments in Marboré Lake (Oliva-Urcía et al, 2013) and by dating of Holocene morainic deposits (García-Ruiz et al, 2014).…”
Section: Study Area and Review Of Previous Research On The Monte Perdmentioning
confidence: 99%
“…En la alta montaña no se observa un cambio sedimentario evidente (Lago de Marboré, Oliva-Urcia et al, 2013), pese a que, sin embargo, sí se ha detectado cierto descenso en la proporción de caducifolios (más sensibles que las coníferas a un incremento de aridez y descenso de temperaturas) en los registros palinológicos de Basa de la Mora (Pérez- ), El Portalet (González-Sampériz et al, 2006 y Estaña, así como un claro descenso de la isoterma de 0°C, según el registro de crisofíceas del Lago Redó (Pla & Catalán, 2005), tal como se observa en la Figura 4 B, D, E y F. En otras regiones de la cuenca del Ebro se ha constata- García-Ruiz et al, 2014). B) Reconstrucción de la anomalía de temperatura en altitud a partir de crisofíceas del Lago Redó (Pla & Catalán, 2005).…”
Section: Clima E Impacto Humano Durante El Holocenounclassified
“…Nicolás Martínez (1981) attributed a large accumulation of grey limestone boulders in the Balcón de Pineta to the Late Glacial period, and following Gómez de Llarena (1936), he considered them to be an external moraine. García-Ruiz and Martí-Bono (2001) Recently, sediment cores from the Marboré Lake demonstrated that partial deglaciation of the Marboré Cirque occurred approximately 13 ka ago, as the Marboré Lake was ice-free 12,700 years ago (Oliva-Urcia et al, 2013) The sediment sequence is composed of laminated silts and shows a significant change in depositional environments around 5500 cal yr BP. Cores from La Larri paleo-lake, located 3 km to the east of the Marboré Lake, revealed that the paleo-lake developed > 35 ka ago when the valley was dammed by a lateral moraine of the Cinca Valley, and it was drained when the moraine was breached around 11 ka ago (Salazar-Rincón et al, 2013).…”
Section: A) the Glacial Evolution Of The Marboré Cirque According To mentioning
confidence: 99%